2021
DOI: 10.1155/2021/6647277
|View full text |Cite
|
Sign up to set email alerts
|

Keeping an Eye on Bisphosphonate Therapy in Myeloma: A Case Report of Ocular Inflammation Postzoledronic Acid Infusion

Abstract: Bisphosphonates have evolved over the past decades from oral to more potent intravenous preparations. Along with significant paradigm shift in the management of myeloma over the past years, stronger nitrogen-containing bisphosphonates, due to their antiresorptive action on the bones, have found their way as a key and integral part in the management of bone disease in myeloma. Multiple randomized controlled trials have established efficacy of bisphosphonates in reducing skeletal-related events in myeloma. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The exact pathogenesis of these adverse reactions, especially scleritis, remains unclear; some studies suggest that the drug may be secreted by the lacrimal gland into tears, causing transient irritation to the mucosa, leading to the release of intraocular cytokines and other acute-phase proteins, or activation of γδT cells within the eye socket. 10 The patient in this case was diagnosed with primary osteoporosis, with a clear history of zoledronic acid use. Within 48 h of medication administration, the patient presented with bilateral eye redness and severe eye pain, exacerbated at night and radiating to the head.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The exact pathogenesis of these adverse reactions, especially scleritis, remains unclear; some studies suggest that the drug may be secreted by the lacrimal gland into tears, causing transient irritation to the mucosa, leading to the release of intraocular cytokines and other acute-phase proteins, or activation of γδT cells within the eye socket. 10 The patient in this case was diagnosed with primary osteoporosis, with a clear history of zoledronic acid use. Within 48 h of medication administration, the patient presented with bilateral eye redness and severe eye pain, exacerbated at night and radiating to the head.…”
Section: Discussionmentioning
confidence: 95%
“…Faryal et al reported a case where bisphosphonate therapy was used to treat severe ocular inflammation caused by multiple myeloma, with the patient showing a significant reduction in eye swelling and pain 3 days after intravenous administration of methylprednisolone 500 mg once daily. 10 Upon discharge, the patient was prescribed oral prednisolone 60 mg, gradually tapering every 3 days until symptoms subsided. Additionally, studies have found that judicious use of topical eye drops can help prevent posterior synechiae, alleviate ciliary muscle paralysis and spasms, decrease exudation, and reduce intraocular pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations